Developing Ideas in Writing Paragraphs using Brainstorming techniques: An Action Research - Dahniar, Dahniar Dahniar; Nurpahmi, Sitti (Universitas Islam Negeri Alauddin Makassar, 2023)
This research discussed about the use of brainstorming technique to improve students’ developing ideas in writing a paragraph at madrasah Aliyah Madani Pao-Pao, Gowa Regency. It aimed to find the improvement of students’ developing ideas in writing a paragraph and the students’ participation towards the use of brainstorming technique to develop the students’ ideas in writing. The researcher conducted a Classroom Action Research (CAR). The researcher conducted two cycles, where each cycle consisted of three meetings. It was done at second grade students at Madrasah Aliyah Madani Pao-Pao. The subjects of this research were thirty students. The instruments used to collect the data were observation checklist and test. The assessment of the test result was focused on the students’ developing ideas in writing a paragraph. The research findings indicated that the use of brainstorming technique was effective and significant in increasing the students’ writing ability based on unity, logic communication/knowledge, and cohesion/coherence. It was proved by the students’ score from the competence test. The first cycle showed that only 10% students got the good score it means that the implementation of brainstorming technique was not successful yet, but in the second cycle 75% students got successful, in the second cycle students was had greater means score improvement than the first, it means that the students have the improvement in writing paragraph from the first cycle to the second cycle. Second, from the result of observation, it showed that majority of the students’ participation during the teaching learning process creates the positive atmosphere in the classroom, and the students also became active in exploring and finding as many as possible ideas they had gotten. Based on the result of this research, the researcher suggests that brainstorming technique can be used as an educational technique in teaching writing especially in teaching writing paragraph type.